Correlated response to selection for litter size environmental variability in rabbits' resilience. (26th February 2019) - Argente, M. J.; García, M. L.; Zbyňovská, K.; Petruška, P.; Capcarová, M.; Blasco, A.
Abstract : Resilience is the ability of an animal to return soon to its initial productivity after facing diverse environmental challenges. This trait is directly related to animal welfare and it plays a key role in fluctuations of livestock productivity. A divergent selection experiment for environmental variance of litter size has been performed successfully in rabbits over ten generations. The objective of this study was to analyse resilience indicators of stress and disease in the divergent lines of this experiment. The high line showed a lower survival rate at birth than the low line (−4.1%). After correcting by litter size, the difference was −3.2%. Involuntary culling rate was higher in the high than in the low line (+12.4%). Before vaccination against viral haemorrhagic disease or myxomatosis, concentration of lymphocytes, C-reactive protein (CRP), complement C3, serum bilirubin, triglycerides and cholesterol were higher in the high line than in the low line (difference between lines +4.5%, +5.6 µg/ml, +4.6 mg/ml, +7.9 mmol/l, +0.3 mmol/l and +0.4 mmol/l). Immunological and biochemical responses to the two vaccines were similar. After vaccination, the percentage of lymphocytes and CRP concentration were higher in the low line than in the high one (difference between lines +4.0% and +13.1 µg/ml). The low line also showed a higher increment in bilirubin and triglycerides than the high line (+14.2 v . +8.7 mmol/l for bilirubin and +0.11 v . +0.01 mmol/l for triglycerides); these results would agree with the protective role of bilirubin and triglycerides against the larger inflammatory response found in this line. In relation to stress, the high line had higher basal concentration of cortisol than the low line (+0.2ng/ml); the difference between lines increased more than threefold after the injection of ACTH 1 to 24, the increase being greater in the high line (+0.9 ng/ml) than in the low line (+0.4 ng/ml). Selection for divergent environmental variability of litter size leads to dams with different culling rate for reproductive causes and different kits' neonatal survival. These associations suggest that the observed fitness differences are related to differences in the inflammatory response and the corticotrope response to stress, which are two important components of physiological adaptation to environmental aggressions.